The Problems of Fulfilling the Rights of Victims of Obscene Crimes - Agustanti, Rosalia Dika; Wahyuningsih, Yuliana Yuli; Lewoleba, Kayus Kayowuan (SASI, 2022)
Introduction: Perpetrators of obscene acts have carried out various criminal acts. Obscene acts are included in sexual violence that results in physical and psychological suffering.Purposes of the Research: This study aims to analyze the fulfillment of the rights of victims of obscene acts, whether it is appropriate or not. This is based on the phenomenon of indecent acts; the more extended the number of victims increases.Methods of the Research: This study uses a normative juridical method with a statute and case approach.Results of the Research: The results of the study indicate that the rights of victims of obscene acts have been regulated and guaranteed in the 1945 Constitution of the Republic of Indonesia, the Law on Human Rights, the Law for the Protection of Witnesses and Victims and the Act on the Crime of Sexual Violence. However, the problem is in the fulfillment of these rights, even though constitutionally, the duties and obligations of fulfilling the rights of victims are borne by the State, which in this case is in the components of the Criminal Justice System, the Ministry of Law and Human Rights, the Ministry of Women's Empowerment and Child Protection, The National Commission on Human Rights, the National Commission on Violence Against Women and the Witness and Victim Protection Agency. The importance of supervision and compliance with the application of rights in everyday life will determine how successful the State is in carrying out its obligations in fulfilling the requests of victims. So it is essential to cooperate between Ministries, Institutions, National Commissions, and law enforcement officials to realize the fulfillment of the rights of victims of criminal acts of obscenity.